2005
DOI: 10.1111/j.1365-2621.2005.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Batch kinetics and modelling of ethanolic fermentation of whey

Abstract: The fermentation of whey by Kluyveromyces marxianus strain MTCC 1288 was studied using varying lactose concentrations at constant temperature and pH. The increase in substrate concentration up to a certain limit was accompanied by an increase in ethanol formation, for example, at a substrate concentration of 10 g L )1 , the production of ethanol was 0.618 g L )1 whereas at 50 g L )1 it was 3.98 g L )1 . However, an increase in lactose concentration to 100 g L )1 led to a drastic decrease in product formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Thus, relevant parameters of Monod kinetics such as the maximum specific growth rate (µ max ), the saturation constant (K s ) and the yield of biomass (Y x/s ) can be considered as passport data for a particular organism [26]. Several kinetic models have been developed, which describe the ethanol production by different K. marxianus strains on lactose -containing substrates [27][28][29][30], including the strain DSM 5422 [12]. However, these models appear as differently structured, may contain quite distinctive parameters, as well as often disregard the possible effects of product and/or substrate inhibition [12; 27] and remain restricted by too narrow range of substrate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, relevant parameters of Monod kinetics such as the maximum specific growth rate (µ max ), the saturation constant (K s ) and the yield of biomass (Y x/s ) can be considered as passport data for a particular organism [26]. Several kinetic models have been developed, which describe the ethanol production by different K. marxianus strains on lactose -containing substrates [27][28][29][30], including the strain DSM 5422 [12]. However, these models appear as differently structured, may contain quite distinctive parameters, as well as often disregard the possible effects of product and/or substrate inhibition [12; 27] and remain restricted by too narrow range of substrate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The K. marxianus strain MTCC 1288 from crude cheese whey containing 35 g L -1 of lactose at 34°C and pH maintained at 4.5 produced 2.10 g L -1 of ethanol and 8.9 g L -1 of cell mass (Zafar & Owais, 2006). The ethanol production from medium containing 50 g L -1 of lactose by the same strain was 3.98 g L -1 and cell mass reached 10.34 g L -1 , in the same temperature and pH conditions (Zafar et al, 2005). Another studies reported ethanol concentrations of ca.…”
Section: Evaluation Of Potential Etdlt1 Strain For Ethanol Productionmentioning
confidence: 77%
“…This is due to the energy savings achieved through the reduction of the expensive cooling and sterilization processes. Several reports revealed inhibitory effects and related problems in the fermentation of concentrated carbon, particularly slow fermentations and high residual sugar (Gawel & Kosikowski, 1978;Janssens et al, 1983;Vienne & von Stockar, 1985;Kamini & Gunasekaran, 1987;Grubb & Mawson, 1993;Dale et al, 1994;Silveira et al, 2005;Zafar et al, 2005;Ozmihci & Kargi, 2007). Main cause of these problems is osmotic sensitivity and low ethanol tolerance (Janssens et al, 1983;Vienne & von Stockar, 1985;Grubb & Mawson, 1993;Zafar et al, 2005).…”
Section: Isolation and Primary Screening Of Yeastmentioning
confidence: 99%
“…The fermentation of cheese whey was optimized with respect to temperature, pH and rpm. This study will help in managing the dairy waste product in Nepal to convert into value added product which can be used as fuel, mouth wash, hospital solvents, perfumes etc 7,8 .…”
Section: Introductionmentioning
confidence: 99%